Um Estudo Sobre a Abordagem do Design Thinking nas Universidades - Canedo, Edna Dias; Almeida, Frederico Viana (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Design Thinking proposes an innovation model, focused on creativity and with a potential for positive results to the universities that seek to increase their capacity to develop students, as it contemplates methods of investigation and development of high resolution in the users. The objective of this paper is to develop a study related to the level of students' knowledge related to Design Thinking and knowledge about the subject. For this, the project includes bibliographical research on innovation, design and Design Thinking and a research with some students of Information Technology (IT). The results obtained in this study demonstrate that the implementation of a systematic system of Design Thinking in the universities, requires several changes in the academic culture. However, the model has the capacity to generate positive results in relation to the development of innovative solutions, since it supports in advanced methods of understanding and generating ideas focused on the user and their needs.